Postoperative analgesia with ropivacaine and dexmedetomidine for ultrasound-guided fascia iliaca compartment block after arthroscopic knee surgery - Li, Ying (Saudi J Anaesth, 2019)
OBJECTIVE: The objective of this study is to evaluate the postoperative analgesic effect of a combination of ropivacaine and dexmedetomidine for ultrasound-guided fascia iliaca compartment block (FICB) after knee arthroscopy. MATERIALS AND METHODS: Forty patients scheduled for knee arthroscopy were randomized to receive either 30 ml of 0.25% ropivacaine alone (Group A, n = 20) or combined with dexmedetomidine 1 μg/kg (Group B, n = 20). Pain intensity was evaluated using the visual analogue scale (VAS), at rest and during activity at 4, 6, 8, 12, and 24 h after surgery. Level of consciousness was evaluated using the Ramsay sedation score. Time to first analgesic request after surgery, the dose of analgesic used in the first 24 h after surgery, variation of heart rate, and adverse reactions were also recorded. RESULTS: VAS scores at 6 and 12 h after surgery were significantly lower in Group B compared to Group A (P < 0.05). No significant difference was observed in the Ramsay sedation score or time to first analgesic request after surgery (P > 0.05). The total dose of analgesic used in the first 24 h after surgery was higher in Group A than in Group B. The incidence of bradycardia was higher in Group B compared to Group A. No adverse reactions were observed in either group. CONCLUSION: FICB with a combination of ropivacaine and dexmedetomidine resulted in significant reduction of VAS scores with lower postoperative analgesic requirement after arthroscopic knee surgery. No adverse reactions or complications were noted except for lower heart rate in Group B patients.